Inquiry oriented electronic student worksheet using liveworksheet on chemical equilibrium material to train analysis thinking skills - Maharani Agustina Arivi; Dian Novita (Jurnal Pijar Mipa, 2023)
This study aimed to describe the feasibility of inquiry-oriented electronic student worksheets using live worksheets on chemical equilibrium material to train the analytical thinking skills of class XI students of Senior High School. The feasibility of the Electronic Student Worksheet is viewed from validity, effectiveness, and practicality. This study uses the Research and Development (R&D) method. A limited trial was conducted in April 2023 for 30 students who had received chemical equilibrium material. The results showed that the validity of the electronic student worksheet was stated to be valid based on the results of the validation of the electronic student worksheet, which received a mode of 4. The practicality of the electronic student worksheet was stated to be practical with a percentage of 93.7%. The electronic student worksheet was declared effective based on the t-test results with a significance level of 5% obtained tcount>ttable of 12.294>2.045, which means Ho was rejected, Ha was accepted, and the N-gain score was 0.7. Based on these results, it can be concluded that electronic student worksheet is appropriate to be used to train analytical thinking skills in chemical equilibrium material.